Phenolic Acids and Antioxidants Profile, Antioxidative Enzymes and Antioxidant Activity of Mango - Panda, Plaban; Dolui, Subhrojit; Banik, Asis K.; Majumder, Anurup; Bhattacharya, Amitava (International Journal of Bio-resource and Stress Management, 2022)
In an effort to evaluate the antioxidative property in mango, a laboratory study was conducted at BCKV, Mohanpur during 2019 with ten varieties of mango selected on the basis of popularity and area coverage. The pulp of the fruit samples harvested at the firm ripe stage showed wide genotypic variability in the contents of antioxidants and activity of the antioxidative enzymes tested. Ascorbic acid and total phenol ranged from 16.20 to 44.26 mg 100 g-1 (around 55% of the RDA of ascorbic acid, on average) and 12.753 to 31.265 mg TE g-1 whereas CAT, PAL, POD and SOD were in the ranges of 15–101, 0.039–0.440, 0.230–2.333 and 3.194–6.695 corresponding units respectively. Antioxidant activity ascertained by DPPH and FRAP assays averaged 5.065 and 14.837 mgTE g-1 respectively. Five phenolic acids, one belonging to hydroxybenzoate (gallic acid) and four to hydroxycinnamates (chlorogenic acid, caffeic acid, p-coumaric acid and ferulic acid) along with t-cinnamic acid were analysed for their contents and ranged from 1282.02–12150.82, 210.34–1189.97, 2.31–56.82, 2.84–317.82, 9.68–41.59 and 3.52–18.59 µg g-1 respectively. The phenolic acids were ranked on the basis of antioxidant activity as gallic acid>ferulic acid>caffeic acid>chlorogenic acid>p–coumaric acid. There were important correlations between paired variables. Principal component analyses done with all the variables revealed that ‘Akhil gooti’ may be selected as the best variety with respect to antioxidative properties followed by ‘Himsagar’ and can be used for the improvement of the varieties and of the human diet.